Le temple de Tirumaṅkaiyālvār à Hampi - Filliozat, Vasundhara (Publications de l'Institut français d'indologie ;, 1976)
Architectural, iconographic, and epigraphic study of the temple in Hampi, Karnataka, dedicated to Tirumaṅkaiyāḻvār, 9th century Vaishnavite Tamil poet.